MUHAMMAD YASIN AL-FADANI DAN KONSTRIBUSINYA DALAM SANAD KEILMUAN ULAMA NUSANTARA - Muhamad R okim, Alfian Dhany Misbakhuddi (UNIVERSUM, 2018)
This article studies on an expert of hadith, Muhammad Yasin al-Fadani, and his contribution toward sanad of Indonesian scholars (ulama). This study is important to see the dynamic hadith study in Indonesia in which had been less attention in 17-20 centuries, and had more attention after Muhammad Yasin al-Fadani performed by bringing knowledge of sanad until Rasullullah saw. Muhammad Yasin al-Fadani is an expert of hadith in Indonesia having some degrees such as Bakhr al-‘ulu>m (knowledge ocean), ‘Alam al-Di>n (religious reference), Musnid al-Hijaz (expert of sanad from Hijaz land), and the most popular degree is musnid al-Dunnya ‘ala> al-It}laq (ulama of sanad expert in the world) Keywords: Muhammad Yasin Al-Fadani, sanad of ulama, Hadith study, Islam in Indonesia